Analysis of endoscopic third ventriculostomy patency by MRI: value of different pulse sequences, the sequence parameters, and the imaging planes for investigation of flow void - (:unkn) unknown (SPRINGER, 2011)
The aim of the study is to evaluate the efficiency of turbo spin-echo (TSE), three-dimensional constructive interference in the steady state (3D CISS) and cine phase contrast (Cine PC) sequences in determining flow through the endoscopic third ventriculostomy (ETV) fenestration, and to determine the effect of various TSE sequence parameters. The study was approved by our institutional review board and informed consent from all patients was obtained. Two groups of patients were included: group I (24 patients with good clinical outcome after ETV) and group II (22 patients with hydrocephalus evaluated preoperatively). The imaging protocol for both groups was identical. TSE T2 with various sequence parameters and imaging planes, and 3D CISS, followed by cine PC were obtained. Flow void was graded as four-point scales. The sensitivity, specificity, accuracy, positive and negative predictive values of sequences were calculated. Bidirectional flow through the fenestration was detected in all group I patients by cine PC. Stroke volumes through the fenestration in group I ranged 10-160.8 ml/min. There was no correlation between the presence of reversed flow and flow void grading. Also, there was no correlation between the stroke volumes and flow void grading. The sensitivity of 3D CISS was low, and 2 mm sagittal TSE T2, nearly equal to cine PC, provided best result. Cine PC and TSE T2 both have high confidence in the assessment of the flow through the fenestration. But, sequence parameters significantly affect the efficiency of TSE T2.
Keywords: Endoscopic third ventriculostomy; Fenestration patency; Flow void; TSE; Cine PC; CINE PHASE-CONTRAST; CSF FLOW; OBSTRUCTIVE HYDROCEPHALUS; FUNCTIONAL-ANALYSIS; ARTIFACT REDUCTION; OUTCOME ANALYSIS; STEADY-STATE; MANAGEMENT